TECHNICAL DIAGNOSTICS OF COMPLEX TECHNICAL OBJECTS - Kuzavkov, Vasyl; Khoroshko, Volodymyr; Iankovskii, Oleg (Ukrainian Information Security Research Journal, 2023)
The availability of an effective diagnostic system is a necessary condition for the trouble-free functioning of any technical system. However, it should be noted that the cost of development and maintenance of such systems does not allow creating them in mass quantities. The paper proposes a construction option and an algorithm for the functioning of an automated system for solving the problems of technical diagnostics of complex technical objects. The structure of the control system proposed in the work is able to ensure the performance of all tasks of technical diagnostics - control of the technical condition, localization of malfunctions, forecasting of the technical condition of the object of control. The use of computing tools as part of the control system makes it possible to obtain a unified device with a variable structure of both hardware and software components. The thus achieved universality and flexibility of the automated diagnostic system as a device with software control ensures its wide use in systems of technical diagnostics and control of complex objects.